2019
DOI: 10.1016/j.bjorl.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Repair of post-laryngectomy pharyngocutaneous fistulas using a pectoralis major flap

Abstract: The pectoralis major flap is a useful approach to repair pharyngocutaneous fistula. Placing salivary tubes during fistula repair significantly reduces hospital stay and complication severity in case of pharyngocutaneous fistula recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
(34 reference statements)
0
11
0
1
Order By: Relevance
“…En nuestra serie, ocho pacientes (66%) fueron reconstruidos de esta manera. [13][14][15][16] La gran versatilidad del colgajo ALT permite realizarlo en forma tubular, éste se conecta en la porción superior a la orofaringe residual y en la inferior al esófago proximal. Las fístulas Figura 4: Caso 2.…”
Section: Discussionunclassified
“…En nuestra serie, ocho pacientes (66%) fueron reconstruidos de esta manera. [13][14][15][16] La gran versatilidad del colgajo ALT permite realizarlo en forma tubular, éste se conecta en la porción superior a la orofaringe residual y en la inferior al esófago proximal. Las fístulas Figura 4: Caso 2.…”
Section: Discussionunclassified
“…When a PCF was confirmed, the initial treatment was conservative management involving antibiotic therapy, continuation of enteral nutrition, and daily local wound care. In cases that did not respond adequately to conservative management, pectoralis major flap reconstruction was considered on a case-by-case basis [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…36 It is otherwise suggested in case of large fistulas 20,25 or PCFs with major wound breakdown and vessel exposure. 2,13,35 Guha et al 20 , for example, suggested the use of these pedicled flaps in case of type 2 or 3 fistula (i.e. larger than 0.5 or 2 cm).…”
Section: Pectoralis Major Flap (Pmf)mentioning
confidence: 99%
“…1 Several risk factors have been analyzed in order to understand the etiology of this major complication: previous radiotherapy (RT) or chemoradiotherapy (CHT), type of surgery, T and N stage, a short interval between the end of RT and laryngectomy, hemoglobin levels lower than 125 g/L preoperative as well as postoperative, comorbidities such as diabetes, liver diseases or hypothyroidism, and surgical aspects such as neck dissection, previous tracheotomy, surgical wound infection, resection of the pharynx and its closure after laryngectomy, or the use of non-irradiated tissue to reinforce the pharyngeal suture. [2][3][4][5] The treatment of PCF is crucial in patients who underwent laryngectomy; the persistence of this abnormal communication is associated with delay in adjuvant treatment, prolonged hospital stay, requirement for reoperation, and mortality from, for example, carotid blowout or aspiration pneumonia. The increased incidence of post-laryngectomy PCF in the modern era of organ preservation therapy has driven considerable efforts to develop…”
mentioning
confidence: 99%
See 1 more Smart Citation